Kanabis med dejavnikom tveganja za zdravje in lajšanjem zdravstvenih težav? - Lovrečič, Mercedes (Zdravstveno varstvo, 2006)
Smoking cannabis is a health risk factor. Effects of cannabis use were assessed by the World Health Organisation in a similar manner as those of alcohol and tobacco, and the need was stressed for giving due consideration tothe established science-based standards and conclusions concerning potentially harmful effects of cannabis use on health. No official recommendations for the use of cannabis in medicine have yet been adopted. Medicinal use of cannabis, though rare, is generally not based on convincing results obtained by reliable clinical studies. Individual variability does notallow for generalization of the effects and consequences of cannabis use. Cannabis is listed among those illicit drugs whose potential harmful effects on health need further investigation.
Keywords: Automobile Driving; Avtomobilska vožnja; Cannabinoids; cannabis; Dejavniki tveganja; Kanabinoidi; kanabis; marihuana; Marijuana Abuse; Marijuhana, zloraba; medicina; medicine; Risk Factors; učinki; uporaba